Effects of habitat and time of day on flock size of Turkey Vultures in Cuba (Cathartes aura) - Tryjanowski, Piotr (Zookeys, 2018)
Abstract. In agricultural landscapes, the Turkey Vulture Cathartes aura feeds mainly on carcases of domestic animals. In spring 2017, data on 214 flocks of Turkey vultures were collected in a road survey in Cuba (in total 2384 km). Turkey Vultures were found to be common accross Cuba, but flock size varied between habitats, reaching a maximum of 43 in valleys and 31 in agricultural landscapes with domestic animal farms. Vultures were active throughout the day, but the time of day did not significantly affect flock size. This study corroborates previous studies which suggested that carrion resources located in agricultural habitats and river valleys is crucial for the continued survival of this still abundant species. Changes in Cuba’s socio-political system in the near future will likely impact agricultural practices, and this in turn will likely affect Turkey Vultures. Our study may serve as a baseline against which future population changes and flocking behaviour of Turkey Vultures can be compared.